AMS and rock magnetism in the Caviahue-Copahue Volcanic Complex (Southern Andes): Emission center, flow dynamics, and implications to the emplacement of non-welded PDCs - Haag, Maurício Barcelos (2021)
Fil: Haag, Mauricio Barcelos. Instituto de Geociências, Universidade Federal do Rio Grande do Sul. Brasil.